Application of Sustainable Village Development in Bukalapak’s Advertisement the Series “Berkawan dengan Zaman” - Jastisia, Irenia; Yani, Aditya Rahman (Arty: Jurnal Seni Rupa, 2022)
Rural communities are synonymous with the lack of welfare and are still lagging behind, so there is a need for community empowerment. Dilain side, Sustainable Development Goals (SDGs) is an international agenda in which Indonesia participates. Referring to the agenda, Bukalapak as one of the companies in Indonesia also made it happen through the advertisement series "Coming with the Times". This study is a qualitative descriptive study aimed at reviewing advertisements and their meaning in detail. As for the theory used is the semiotics of Roland Barthes, which not only unravels denotative and conotative meanings, but myths. Through his theory, this study aims to uncover how a company participates in the achievement of SDGs through the economic welfare of rural communities.